2011
DOI: 10.1103/physrevc.84.041304
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of isospin mixing at a finite temperature in80Zr via giant dipole resonance decay

Abstract: Isospin mixing in the hot compound nucleus 80 Zr was studied by measuring and comparing the γ -ray emission from the fusion reactions 40 Ca + 40 Ca at E beam = 200 MeV and 37 Cl + 44 Ca at E beam = 153 MeV. The γ yield associated with the giant dipole resonance is found to be different in the two reactions because, in self-conjugate nuclei, the E1 selection rules forbid the decay between states with isospin I = 0. The degree of mixing is deduced from statistical-model analysis of the γ -ray spectrum emitted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…For 81 Rb the best-fitting values (see the corresponding FOM in the top right-hand panel of Fig. 2) for the centroid, width, and strength of GDR were found to be E GDR ¼16.4AE0.2MeV, Γ GDR ¼7.0AE0.2MeV, and S GDR ¼ 0.90 AE 0.05, in agreement with the systematics and liquid drop model calculations [15,21].…”
supporting
confidence: 69%
See 3 more Smart Citations
“…For 81 Rb the best-fitting values (see the corresponding FOM in the top right-hand panel of Fig. 2) for the centroid, width, and strength of GDR were found to be E GDR ¼16.4AE0.2MeV, Γ GDR ¼7.0AE0.2MeV, and S GDR ¼ 0.90 AE 0.05, in agreement with the systematics and liquid drop model calculations [15,21].…”
supporting
confidence: 69%
“…[15] the isospin mixing was investigated at N ¼ Z ¼ 40 at T ¼ 3 MeV, while previous works concern CN with smaller N ¼ Z values only. The work on 80 Zr [15] showed that by using the latest prediction of the isospin mixing value (based on EDF models [16]) together with the expression giving the T dependence of the isospin mixing [11], one finds a good agreement with the measured value at T ¼ 3 MeV. This finding indicates that with an additional experimental point at another T one could deduce, from the combined data analysis, the value at T ¼ 0.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a further example, shell-model calculations, intended to predict the location of the driplines, have recently had isospin nonconserving (INC) interactions specifically included [3]. To date, such studies have largely focused on nuclei in the sd and lower fp shells and has involved studies of the energies of analog states (see [4,5] and references therein) as well as studies of the hinderance of E1 decays due to selection rules in N = Z nuclei [6][7][8]. Detailed investigations in the f 7 2 shell region have revealed a need to include an isospin nonconserving (INC) force beyond the Coulomb interaction (see Ref.…”
Section: Introductionmentioning
confidence: 99%